Morphometric analysis using geospatial techniques forpriotrization of the eastern Jeddah sub-watersheds to reduce the risk of flooding and soil erosion - E. M. Al-Juaidi , Ahmed (International Journal of Engineering and Technology, 2024)
The goal of this work is to prioritize Jeddah sub-watersheds using morphometric parameters, the Weighted Sum Approach (WSA), and GIS. Finding the sub-watershed that is most vulnerable to flooding and soil erosion is the goal of priotrizating these watersheds. Major catastrophic floods that struck Jeddah’s watersheds in 2009 claimed 113 lives, destroyed 10,000 homes, and severely damaged 17,000 au-tomobiles. At first, the subwatersheds and streams were generated using the GIS technique, and the morphometric parameters for the sub-watersheds were computed. For nine chosen morphometric parameters, the Pearson's cross-correlation matrix was run with a 5% signifi-cance threshold. Based on the value of the compound factor obtained from WSA, each sub-watershed was assigned a rank level and priority category (Very high, high, medium, low, very low). The results show that SWD-2 and SWD-4 are highly vulnerable to flooding in about 57% of all sub-watershed areas. These two sub-watersheds require emergency flood prevention measures. Sub-watersheds 2 and 4 (SWD-2 and SWD-4) were the main contributors to the devastating floods of 2009 that claimed many lives and destroyed many homes. This shows that although while WSA is straightforward, it nevertheless has a wide range of possible applications in all sub-watersheds that are susceptible to flash floods and soil erosion.